Knowledge and Attitude of Turkish Male Health Care Workers Regarding Human Papillomavirus and Vaccination - Ahmet Doğan; Meryem Sena Toker; Hasan Tahsin Gozdas; Tayibe Bal (American Journal of Men's Health)
This descriptive, cross-sectional survey study aimed to evaluate the knowledge of human papillomavirus (HPV) infection and vaccination, related diseases, vaccination status, and attitudes toward vaccination among Turkish male health care workers (HCWs). The study was planned between June 20 and 30, 2023. A questionnaire was developed by reviewing similar studies to assess the sociodemographic characteristics, knowledge about HPV, vaccination, and attitudes toward vaccination. A total of 322 volunteers (doctors, male nurses, and other allied health personnel such as cleaning staff, patient carers, and technicians) completed the questionnaire. Participants generally provided accurate answers to questions about HPV but often provided incorrect answers regarding vaccination. In addition, the overall HPV knowledge score was significantly higher among vaccinated participants or those willing to be vaccinated than those who were unvaccinated participants and those who were unwilling to be vaccinated ( p  < .05). There was a significant and moderately strong relationship between HPV vaccine knowledge level and willingness to be vaccinated. In addition, the relationship between vaccination status and knowledge level was substantial. Factors such as medical position, age, alcohol use, and regular physical activity were more likely to affect the HPV knowledge levels of assistant HCWs negatively. Vaccine hesitancy was also higher in the 27 to 40 age group. Knowledge about HPV, medical position, number of sexual partners, social habits, views on vaccination, cost, and religious and cultural values directly affect the rate of HPV vaccination and willingness to be vaccinated.